2015
DOI: 10.1016/j.jphs.2015.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine causes vasodilation and hypotension induced by activation of KCNQ-encoded voltage-dependent K+ channels

Abstract: Kynurenine is a potential contributor to hypotension in animal and human sepsis. The present study was designed to examine whether the voltage-dependent K(+) channels encoded by the KCNQ gene family (Kv7 channels) mediate vasodilator effects of kynurenine and whether modulation of these channels ameliorates hypotension caused by this compound. Rat aortas and mesenteric arteries or human omental arteries without endothelium were used. Some rings were incubated with the selective Kv7 channel inhibitor linopirdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
2
35
1
Order By: Relevance
“…Despite only modest effects of acute linopirdine treatment on blood pressure in normotensive rats, we observed that retigabine-induced hypotension was instantaneously reverted with intravenous linopirdine. This finding is in agreement with urodynamic effects of retigabine and linopirdine [24] and with the effects of linopirdine on hypotension induced by kynurenine, a natural tryptophan metabolite that is thought to activate Kv7 channels and which has been implicated in the pathophysiology of sepsis [25]. As such, Kv7 channel modulators may provide an alternative pharmacological approach for the management of hypertensive emergencies, in which drugs that permit rapid, titratable and reversible reduction of blood pressure are highly desirable.…”
Section: Discussionsupporting
confidence: 78%
“…Despite only modest effects of acute linopirdine treatment on blood pressure in normotensive rats, we observed that retigabine-induced hypotension was instantaneously reverted with intravenous linopirdine. This finding is in agreement with urodynamic effects of retigabine and linopirdine [24] and with the effects of linopirdine on hypotension induced by kynurenine, a natural tryptophan metabolite that is thought to activate Kv7 channels and which has been implicated in the pathophysiology of sepsis [25]. As such, Kv7 channel modulators may provide an alternative pharmacological approach for the management of hypertensive emergencies, in which drugs that permit rapid, titratable and reversible reduction of blood pressure are highly desirable.…”
Section: Discussionsupporting
confidence: 78%
“…In aortae and MAs, the effects of L‐kynurenine (± linopirdine) were mimicked by flupirtine, a Kv7 channel activator. Furthermore, the antagonistic effect of linopirdine on either L‐kynurenine‐ or flupirtine‐induced vasorelaxation was not mimicked by 1 mmol L −1 4‐aminopyridine, a blocker of other classes of Kv channels, suggesting that Kv7 channels are specifically required for the L‐kynurenine effect . Impalement recoding of membrane voltage in smooth muscle cells within the MA wall revealed that L‐kynurenine induced an approximately 12 mV membrane hyperpolarization, which was completely reversed by addition of linopirdine, further supporting Kv7 channels as a specific mediator of L‐kynurenine's vasodilator effect .…”
Section: Vasodilator Signaling Via Kv7 Channelsmentioning
confidence: 98%
“…Furthermore, the antagonistic effect of linopirdine on either L‐kynurenine‐ or flupirtine‐induced vasorelaxation was not mimicked by 1 mmol L −1 4‐aminopyridine, a blocker of other classes of Kv channels, suggesting that Kv7 channels are specifically required for the L‐kynurenine effect . Impalement recoding of membrane voltage in smooth muscle cells within the MA wall revealed that L‐kynurenine induced an approximately 12 mV membrane hyperpolarization, which was completely reversed by addition of linopirdine, further supporting Kv7 channels as a specific mediator of L‐kynurenine's vasodilator effect . Finally, intravenous administration of L‐kynurenine (1 mmol L −1 ) to anesthetized male Wistar rats induced about a 35% drop in mean arterial pressure, which was partially reversed following administration of linopirdine (10 μmol L −1 ), providing evidence that these signaling mechanisms may be evident at the systemic level, and that pharmacological targeting of microvascular Kv7 channels may have therapeutic benefit in the treatment of septic shock …”
Section: Vasodilator Signaling Via Kv7 Channelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Because the vasorelaxing action of XA was not entirely blocked by apamin and Ctx, it cannot be excluded that additional types of potassium channels are involved. Of note, the vasorelaxing action of L -kynurenine appears to be mediated by activation of Kv7 voltage-sensitive potassium channels (Sakakibara et al, 2015), although, as opposed to XA, the action of L -kynurenine on blood vessels does not require the integrity of the endothelium (Wang et al, 2010; Sakakibara et al, 2015). It is possible that XA and KYN cause arterial relaxation acting on different types of vessels and via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%